Trends in Neonatal Mortality at Princess Marie Louise Children's Hospital, Accra, and the Newborn Strategic Plan: Implications for Reducing Mortality in Hospital and the Community - Edem M. A. Tette; Edmund T. Nartey; Mame Yaa Nyarko; Abena K. Aduful; Margaret L. Neizer (MDPI AG, 2023)
Background: In low and middle-income countries, close to half of the mortality in children under the age of five years occurs in neonates. Objectives: We examined the trend, medical conditions and factors associated with newborn deaths at the Princess Marie Louise Children's Hospital (PML), Accra, from 2014 to 2017 (4 years). Methods: The study was a cross-sectional study. Data on age, sex, date of admission, date of discharge, cause of death and place of residence of these babies were obtained from the records department. This was transferred into an Access database and analyzed. Components of the Newborn Strategic Plan implemented at the hospital were described. Results: Neonatal sepsis, pneumonia and kernicterus were the major causes of death. Admissions increased and 5.4% of the neonates died, declining from 6.5% in 2014 to 4.2% in 2017 due to deliberate actions to reduce neonatal death. The highest mortality occurred in babies residing in an area more than 1 hour's drive away from the hospital. Conclusion: Implementing the Newborn Strategic Plan was associated with a drop in mortality. A preponderance of community-acquired infections was observed. Thus, locality-specific interventions targeted at known determinants and implementing the newborn strategic plan are essential for reducing neonatal mortality.